The characteristics and mapping algorithm of rectangular vertex chain code - Wulandhari, Lily Ayu (Penerbit UTM, 2007)
Image representation always becomes an important and interesting topic in image processing and pattern recognition. Since introduced by Freeman in 1961, that is known as Freeman Chain Code (FCC) the evolution and improvement of chain code representation scheme has been widely used as a topic of research. In 1999, Bribiesca introduced a new two-dimensional chain code scheme that is called Vertex Chain Code (VCC). An element of this chain indicates the number of cell vertices, which are in touch with the bounding contour of the shape in that element position. The VCC is composed of three regular cells, namely rectangular, triangular, and hexagonal. This chapter describes the characteristic and mapping algorithm one of the VCC cells, namely Rectangular – VCC cell.